2012
DOI: 10.1002/ejoc.201200807
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of [2‐(Trimethylsilyl)ethynyl]pyrazoles Based on Bis(trimethylsilyl)acetylene and Arylacetyl Chlorides

Abstract: A practical approach to the synthesis of [2‐(trimethylsilyl)ethynyl]pyrazoles was developed through condensation of hydrazines with enynones that are easily accessible frombis(trimethylsilyl)acetylene and arylacetyl chlorides. Optimized conditions for reactions with monoarylhydrazines permit the chemoselective formation of 5‐alkynylpyrazoles in high yields (48–94 %). When monoalkylhydrazines or the parent hydrazine is used, mixtures of 3‐ and 5‐alkynylpyrazoles are formed in 73–79 % yields. The method uses ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…As compounds 4a – e possess three electrophilic centers, the formation of different heterocycles in reactions with binucleophiles may a priori be anticipated. Our previous studies showed that the triple bond in compounds 4 was not involved in reactions with hydrazines,6 and therefore we expected that the reactions between enynones 4a – e and arylamidines 7a – e (symmetrical binucleophiles) would lead to pyrimidines 8 as single products, as was indeed observed in all reactions. The triple bond remained intact, as can be seen from the pairs of signals at δ = 80–81 and 83–89 ppm, which correspond to the C≡C fragment, in the 13 C NMR spectra of all the pyrimidines.…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…As compounds 4a – e possess three electrophilic centers, the formation of different heterocycles in reactions with binucleophiles may a priori be anticipated. Our previous studies showed that the triple bond in compounds 4 was not involved in reactions with hydrazines,6 and therefore we expected that the reactions between enynones 4a – e and arylamidines 7a – e (symmetrical binucleophiles) would lead to pyrimidines 8 as single products, as was indeed observed in all reactions. The triple bond remained intact, as can be seen from the pairs of signals at δ = 80–81 and 83–89 ppm, which correspond to the C≡C fragment, in the 13 C NMR spectra of all the pyrimidines.…”
Section: Resultsmentioning
confidence: 60%
“…The severe conditions required for the second step (prolonged heating at 130 °C in Ac 2 O) lead to notable tarring of the reaction mixtures and diminished yields of the desired enynones 4 in comparison with the ethoxymethylation of activated substrates such as 1,3‐dicarbonyl compounds 7. Nevertheless, we isolated compounds 4a – e in moderate yields, and in all cases the ketones 4 were formed as single stereoisomers with the ( E )‐configuration unambiguously established by X‐ray analysis for compound 4a 6…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations